Microstructure and Mechanical Properties of Composites of Bovine _x000D_ Derived Hydroxyapatite (BHA) Reinforced with MgF2_x000D_ - (:unkn) unknown (My University, 2020)
Composites of calcinated bovine bone derived hydroxyapatite (BHA) doped 1 and 2 wt% MgF2 were prepared by a sintering process. Microstructure and crystallographic analyses along with measurements of density, compression strength, and microhardness were carried out in the produced samples. The experimental results indicated a beneficial effect of MgF2 in the matrix of BHA reflected in the significant increase of compression strength and microhardness up to 143 MPa and 313 HV, respectively, achieved after sintering at 1300 0C for 2% MgF2 addition. The presence of MgF2 reduced the onset of sintering towards lower temperatures (i.e. 1100 0C) and increased the stability of hydroxyapatite towards transformation to TCP at 1300 0C. The influence of Mg2+ and Fions in the lattice of hydroxyapatite is discussed.

Kalsine edilmiş sığır kemiğinden elde edilen hidroksiapatit (BHA) ile ağırlıkça% 1 ve ağırlıkça% 2 MgF2 katkılı kompozitleri _x000D_ bir sinterleme işlemi ile hazırlandı. Üretilen numunelerde mikroyapı ve kristalografik analizler ile birlikte yoğunluk, basma _x000D_ mukavemeti ve mikrosertlik ölçümleri yapıldı. Deneysel sonuçlar, % 2 MgF2 ilavesi ve 1300oC'de sinterlemeden sonra elde _x000D_ edilen BHA matrisin, sıkıştırma mukavemeti ve mikro sertlikteki önemli artışa (sırasıyla 143 MPa ve 313 HV'ye kadar) neden _x000D_ olduğunu gösterdi. MgF2'nin varlığı, sinterleme başlangıcını daha düşük sıcaklıklara (~ 1100oC) düşürdü ve hidroksiapatitin _x000D_ 1300oC'de TCP'ye dönüşüme karşı stabilitesini arttırdı. Mg2_x000D_ + ve Fiyonlarının hidroksiapatit örgüsündeki etkisi tartışıldı.
MgF2 ile Güçlendirilmiş Sığır Kaynaklı Hidroksiapatit (BHA) Kompozitlerinin Mikroyapısı ve Mekanik Özellikleri